A New Alkali‐Stable Phosphonium Cation Based on Fundamental Understanding of Degradation Mechanisms. Issue 17 (18th August 2016) - Zhang, Bingzi; Kaspar, Robert B.; Gu, Shuang; Wang, Junhua; Zhuang, Zhongbin; Yan, Yushan
Abstract: Highly alkali‐stable cationic groups are a critical component of hydroxide exchange membranes (HEMs). To search for such cations, we studied the degradation kinetics and mechanisms of a series of quaternary phosphonium (QP) cations. Benzyl tris(2, 4, 6‐trimethoxyphenyl)phosphonium [BTPP‐(2, 4, 6‐MeO)] was determined to have higher alkaline stability than the benchmark cation, benzyl trimethylammonium (BTMA). A multi‐step methoxy‐triggered degradation mechanism for BTPP‐(2, 4, 6‐MeO) was proposed and verified. By replacing methoxy substituents with methyl groups, a superior QP cation, methyl tris(2, 4, 6‐trimethylphenyl)phosphonium [MTPP‐(2, 4, 6‐Me)] was developed. MTPP‐(2, 4, 6‐Me) is one of the most stable cations reported to date, with <20 % degradation after 5000 h at 80 °C in a 1 m KOD in CD3 OD/D2 O (5:1 v / v ) solution. Abstract : Substituent‐induced stability : An alkali‐stable quaternary phosphonium cation is designed to eliminate substituent degradation while maintaining desirable electronic and steric properties of the nine phenyl substituents. It is 64 times as stable as the benchmark cation, making it one of the most stable cations for hydroxide exchange membranes.